RESISTENSI DAN FLEKSIBILITAS PENDUDUK PERDESAAN LAHAN KERING - Tukiran Tukiran; Agus Susanto (Populasi, 1999)
The various forms of crises that have occurred at national and regional scale have not yet been fully felt in the dry areas, particularly in Gunung Kidul, Yogyakarta Special Province. Interesting, these rural dry areas have been very resistant and flexible in facing the impact of the economic crisis. The major factor that has made this possible is self-reliance, which was triggered by the low degree of dependence on other places for various necessities. Most of the places provide them for themselves. As far as providing basic necessities are concerned, the rural community has not yet shown symptoms of anxiety. Some saving has actually been carried out, but there is not yet any sufficient evidence of drastic decline in quality and quantity. From the beginning of the economic recession until today, saving for general (public) benefit, especially in social issues – (communalism), which is usually difficult to establish, could be easily accepted with no resistance from the community. The prospect of the rural economic sector of the dry lands can be divided into two broad categories, that is the survivor sector, and the inferior sector. The survivor sector comprises of economic activities that will continue to persist even if there is no growth, like agriculture and animal husbandry. The inferior sector on the other hand, include those activities, which are not very effective in addressing the economic crisis, and even potentially risk vanishing, like industry, trade and service sectors. The biggest impact is however, more felt in the non- economic sector, particularly those to do with services like health and family planning.